2015
DOI: 10.5606/kbbihtisas.2015.65768
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of multimodality approach to sudden hearing loss

Abstract: Addition of ITS to systemic steroid and HBO treatment may yield better results in patients with SHL. However, ITS injection seems beneficial for patients with profound SHL.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 26 publications
0
8
0
Order By: Relevance
“…Both treatment arms showed significant improvements in hearing, but there was no significant difference between the treatment arms (55% in group 1 vs 63% in group 2). 189 HBOT as Salvage Therapy. HBOT has also been studied as salvage therapy for those not responding to other primary treatments.…”
Section: Supporting Textmentioning
confidence: 99%
See 1 more Smart Citation
“…Both treatment arms showed significant improvements in hearing, but there was no significant difference between the treatment arms (55% in group 1 vs 63% in group 2). 189 HBOT as Salvage Therapy. HBOT has also been studied as salvage therapy for those not responding to other primary treatments.…”
Section: Supporting Textmentioning
confidence: 99%
“…Both treatment arms showed significant improvements in hearing, but there was no significant difference between the treatment arms (55% in group 1 vs 63% in group 2). 189…”
Section: Key Action Statementsmentioning
confidence: 99%
“…[11,12] To date, none of the treatment options has shown superiority to one another in randomized clinical trials. [13] Although there are numerous studies showing significantly higher rates of hearing improvement with the use of oral steroids; [11,14] the efficacy of salvage treatment options still remains unclear. Intratympanic steroid injection is an effective, safe, and well-tolerated officebased procedure for the treatment of SSNHL as the primary treatment or salvage treatment which can avoid the potential adverse effects of systemic steroids.…”
Section: Discussionmentioning
confidence: 99%
“…Patients responding to therapy highest in combination group (84%) compared to HBOT and IVS (70% and 68%) Edizer [ 113 ] 2015 ISSHL RS SS vs SS + LMWH vs SS + HBOT vs SS + LMWH + HBOT (MT) No NA NA HBOT: 31.2 MT: 31.2 Time till treatment > 10 days had a worse prognosis. Age, degree of hearing loss and hypertension affect the prognosis of ISSHL Naiboğllu [ 112 ] 2015 ISSHL PS SS + HBOT vs SS + HBOT + ITS ≤ 3 No 23.9 30.8 30 Only beneficial effect of ITS in profound hearing loss Attanasio [ 111 ] 2015 ISSHL PS HBOT + ITS < 15 No 29.4 31.9 59.3 No difference between HBOT treatment once or twice a day Yildirim [ 110 ] 2015 ISSHL RS IVS + IV piracetam + HBOT Three groups ≤ 7, (8-14), > 14 No 18.9 34.6 NA Treatment within 14 days significantly better than after 14 days Guha [ 155 ] 2015 ISSHL PS HBOT monotherapy NA No 17.6 22....…”
Section: Clinical Use Of Hyperbaric Oxygen Therapymentioning
confidence: 99%
“…They found no differences between the two delivery strategies. Naiboğllu et al found that addition of intratympanic corticosteroids to HBOT with systemic corticosteroids does not result in better recovery [ 112 ].…”
Section: Clinical Use Of Hyperbaric Oxygen Therapymentioning
confidence: 99%